Modulation of the binding of basic fibroblast growth factor and heparanase activity by purified λ-carrageenan oligosaccharides. (10th July 2015) - Niu, Ting-Ting; Zhang, Dong-Sheng; Chen, Hai-Min; Yan, Xiao-Jun
Highlights: Firstly purified and identified λ-carrageenan oligosaccharides. λ-Carraheptaose interfere with bFGF binding to receptor and inhibit heparanase activities. λ-Carraheptaose inhibits bFGF induced cell proliferation and heparanase activity. λ-Carraheptaose has slow association and slow dissociation characterization. Abstract: Inhibitors of angiogenesis and tumor metastasis are increasingly emerging as promising agents for cancer therapy. Here, we report λ-carrageenan oligosaccharides (λ-COs), highly-sulfated oligosaccharides acting as a basic fibroblast growth factor (bFGF) antagonist and heparanase inhibitor. λ-COs with degree of polymerization (DP) from 2 to 8 degraded by λ-carrageenase were separated and purified. The structures were identified by mass spectrometry. The activities of λ-COs are closely related with DP. λ-COs showed no cytotoxicity, but inactivated bFGF-induced cell proliferation; among them, λ-carraheptaose showed highest capability. Only λ-carraheptaose can effectively bind to bFGF. Binding kinetics showed that λ-carraheptaose and suramin had different binding modes, i.e., suramin displayed a fast association and fast dissociation, but λ-carraheptaose exhibited a slow association and slow dissociation. In addition, λ-COs showed the highest heparanase inhibitory ability and abolished the endothelial cell invasion. Thus, λ-COs may provide a tool to develop of new carbohydrate-based therapeutics against cancer and angiogenesis.